Africa Agriculture Status Report 2014 Launch - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 2 September 2014 the Africa Agricultural Status Report was launched in Addis Ababa and The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), East Africa program leader who was a panelist during the launch. The report was officially launched by H.E. John Kufour, the UN Secretary-General's Special Envoy on Climate Change during the Alliance for a Green Revolution Forum 2014. Photos S.Kilungu (CCAFS)